Negotiating Comprehension: Surakarta Elementary Teachers' Perspectives on Reading Pedagogy in the Age of AI - Maulida, Nimas Ayu Nawal; Muamaroh, M; Ratih, Koesoemo; Hikmat, Mauly Halwat (Universitas Muhammadiyah Surakarta, 2025)
This qualitative study explores how elementary English teachers negotiate their understanding and practice of reading pedagogy in an era where artificial intelligence tools can instantaneously summarize, analyze, and interpret complex texts. Drawing on reader-response theory and postmodern pedagogical frameworks, this research examines the tensions between traditional notions of